El valor del multiculturalismo en educación - Arregui, Jorge V. (Revista Española de Pedagogía, 2018)
Both the European integration and the demands of the cultural minorities within each state led us to live in multicultural societies. The paper analyses the different consequences upon educational model of considering multiculturalism as an inescapable fact or as something intrinsically good. The consideration of multiculturalism as a fact leads to establish a sharp distinction between the public and the private spheres of human life and to reduce education to the public realm. Against this view, the article argues in favour of considering multiculturalism as a good looking for a right approach of the problem of the relationships between culture and nature. Against the illustrated uniformitarian view of human nature, it is defended with Aristotle a teleological one. This teleological view enables us to understand why the very existence of a plurality of cultural traditions is, as Dilthey claims, per se good.
Keywords: valor; multiculturalismo; educación; Revista Española de Pedagogía